DAKWAH AS A PROFESSION: THE IMPACT OF POPULARITY AND ITS CHALLENGES FOR PREACHERS - Asrul Harahap (Pascasarjana UIN Sjech M. Djamil Djambek Bukittinggi, 2025)
In recent years, dakwah (Islamic preaching) in Indonesia has undergone significant developments, evolving from merely spreading religious values to becoming a profession with social, cultural, economic, and political implications. With the rise of social media and technology, dakwah has gained widespread attention, giving preachers (da’i) considerable influence, both within the Muslim community and society at large. However, this popularity presents new challenges for da’i in maintaining their integrity and professionalism, especially when faced with material temptations and political exploitation of their influence. This study aims to explore how da’i can maintain their integrity and professionalism in the face of such challenges, and what strategies they employ to stay focused on their religious mission amidst the growing complexities of the world. This research employs a qualitative approach using document analysis and case studies of three prominent da’i figures: Ustadz Adi Hidayat, Ustadz Abdul Somad, and Gus Miftah. The findings indicate that da’i who are able to maintain their integrity and professionalism tend to have a stronger and deeper influence on their followers. They establish a stronger trust-based relationship with their audiences, which enhances the effectiveness of their preaching. Despite material temptations and involvement in politics, these da’i remain committed to preserving the essence of dakwah, staying true to religious principles without deviating from their original mission. Dakwah di Indonesia telah mengalami perkembangan yang signifikan dalam beberapa tahun terakhir, tidak hanya sebagai sarana penyebaran nilai-nilai agama, tetapi juga sebagai profesi yang memiliki dampak sosial, budaya, ekonomi, dan politik. Dengan berkembangnya media sosial dan teknologi, dakwah semakin mendapat perhatian luas, di mana para da’i memiliki pengaruh besar, baik di kalangan umat Islam maupun masyarakat secara umum. Namun, popularitas ini membawa tantangan baru bagi da’i dalam mempertahankan integritas dan profesionalisme mereka, terutama ketika dihadapkan pada godaan materi dan politisasi dakwah. Penelitian ini bertujuan untuk memahami bagaimana da’i dapat mempertahankan integritas dan profesionalisme dalam menghadapi godaan tersebut, serta strategi apa yang digunakan oleh da’i dalam menjaga fokus dakwah mereka di tengah tuntutan dunia yang semakin kompleks. Metode yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan analisis dokumen dan studi kasus terhadap tiga tokoh da’i terkenal, yaitu Ustadz Adi Hidayat, Ustadz Abdul Somad, dan Gus Miftah. Hasil penelitian menunjukkan bahwa da’i yang dapat menjaga integritas dan profesionalisme cenderung memiliki pengaruh yang lebih besar terhadap jamaah. Mereka mampu menciptakan hubungan kepercayaan yang kuat dan mendalam dengan audiens, yang mempengaruhi efektivitas dakwah mereka. Meski ada godaan materi dan keterlibatan politik, para da’i ini tetap berkomitmen untuk menjaga esensi dakwah dan tidak melenceng dari prinsip-prinsip agama.